Wellbeing and Smart Textiles: Reflecting on Collaborative Practices and the Design Process. (2nd January 2016) - Briggs-Goode, Amanda; Glazzard, Martha; Walker, Sarah; Kettley, Sarah; Heinzel, Tincuta; Lucas, Rachel
Abstract: This paper reports on an inter-disciplinary, EPSRC funded research project, "An Internet of Soft Things" (IoSofT) which seeks to bring soft surfaces, smart textiles and wearable technologies to join the Internet of Things debate. The project involves researchers from academic disciplines: design, computing and mental health in collaboration with a project partner, the Nottinghamshire network of the mental health charity, Mind. This paper will reflect upon the research project and specifically the approach the authors have taken to collaborative textile practice and how this has impacted upon the design process. This project was conducted through a number of practical workshop activities with Mind service user groups. The workshops focused upon the crafting of personalized textile objects with soft switches and various output and also recorded the clients' descriptions of their sense of ownership, awareness of their own and others' emotions and behaviours. The workshops included the researchers' reflections and observations to enable further understanding of how this community invests meaning in material things and modes of expressive output. The aim of the research project is to use textile craft practice and smart materials alongside therapeutic approaches to contribute to the development of a wellbeing and mental health toolkit to support future client work for Mind.